PENGGUNAAN MEDIA AUDIO VISUAL BERBASIS ANIMAKER TERHADAP HASIL BELAJAR MENYIMAK PADA PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR INPRES KATANGKA 1 KABUPATEN GOWA - Nurhaedah, Nurhaedah; Alam, Muh.; Nurbina, Nurbina; Alfah, Siti; Feblina, Ayu Rahayu; Pariati, Pariati (Jurnal Ilmiah Amanah Akademika, 2022)
Indonesian language learning includes 4 aspects of skills, namely: speaking, writing, reading, and listening. Of the 4 skills, it is very important to learn so that students can communicate effectively both orally and in writing. The use of learning media is also a way to make learning more effective. The purpose of this study was to see how much influence the Video Audio Visual Animaker learning media had on students' listening learning outcomes in Indonesian class III students at SD Inpres Katangka 1. This study used a Quasi Experimental research model. type of post test only control design with location in Inpres Katangka 1 Elementary School, Gowa Regency. The research subjects were third grade students of Inpres Katangka 1 Elementary School, Gowa Regency as many as 28 students of class A as the control class and 28 students of class B as the experimental class in the form of 10 test items used in the form of post test control and post test experiments. the use of audio-visual animaker media is more influential than using conventional media in the form of listening materials. This can be seen from the results of this study proving that the control post test with an average of 44.71 and the experimental post test with an average of 76.40 Therefore, it is concluded that the use of animaker audiovisual media affects the learning outcomes of listening to third grade elementary school students.